Grundtvigs salmer før Luther - Elbek, Jørgen (Grundtvig-studier, 1981)
Grundtvig’s Hymns before Luther - A Paper By Jørgen Elbek The paper examines a number o f Grundtvig’s reworkings partly of David’s psalms, partly o f the early Greek, medieval Latin and old Danish hymns on the basic theme that, in contrast to the Danish hymnwriters Kingo and Brorson from the 17th and 18th centuries, but in accordance with Hans Christensen Sthen from the 16th century, Grundtvig’s hymnwriting revives the harmony o f nature in the medieval folk-poems, but as a nature that is redeemed and set free by the divine truth - not a holy but a hallowed nature, Den signede dag (The Blessed Day) as the title o f Grundtvig’s best-known hymn goes. In his reworking o f the Latin supplications o f the Holy Spirit, Grundtvig shows how harmony arises between feeling and intellect, so that mankind sees the deeper connection and can realise it in human life. It was Grundtvig’s belief that everyday life should be a divine service - the religious practice that Protestantism otherwise lacked.